Subjective assessment of the quality of nursing care in terms of postoperative pain in patients undergoing surgical intervention - Juszczak, Katarzyna; Jaracz, Krystyna; Kuberka, Izabela (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
Aim of the study was an assessment of the quality of nursing care in the context of post-operative pain in patients after surgical intervention Material and methods: The study group consisted of 291 patients surgical wards – 162 women (55.7%) and 129 men (44.3%) aged 18 to 86 years (mean age 51.7, SD = 15.3). The study used the Polish version of the Strategic and Clinical Quality Indicators in Postoperative Pain Management (SCQIPP). Results : The average results of the general scale SCQIPP in the group of patients was 56.9 points. (SD = 0.69) (scale range 14–70). Scoring for the individual subscales were as follows: Communicating – 12.2 points (SD = 2.5), Action – 14.1 points (SD = 3.8), Trust – 17.6 points (SD = 2.8) and the Environment – 12.8 points (SD = 2.4). Conclusions : The level of quality of care in the context of post-operative pain level was high. Identified areas for improvement in the quality of care within two subscales: Action and Communication. It seems especially important to promote measures for greater collaboration between patients and staff, and for systematic, quantitative assessment of the surgery.